Giant uterine fibroid: a rare differential diagnosis for an abdominopelvic mass - P., Gayathre S.; T., Sivakumar; S., Aashmi Chandrikaa; ., Prashanth (International Surgery Journal, 2021)
Uterine leiomyomas also called as fibroid uterus are commonest tumors of the female genitourinary tract, however the occurrence of a giant uterine fibroid is rare. The giant uterine leiomyomas pose a great diagnostic as well as surgical challenge due to its size, vague nonspecific symptoms and the inadvertent injury to the adjacent organs during surgery. Here we would like to report a case of a 42 years female, known psychiatric patient with complaints of progressive abdominal distension for 5 years with rapid enlargement in the past 1 year with amenorrhea for 6 months and constipation for 2 months. Pre-operatively patient was diagnosed with ovarian malignancy and was proceeded with staging laparotomy where the mass was found to be arising from the uterus. Patient underwent total abdominal hysterectomy with bilateral salpingo oophorectomy and pathological examination revealed fibroid uterus with cystic degeneration. Post-operatively the patient recovered well and was discharged and on follow up examination was found to have returned to her normal life.